Transcriptome of the Krushinsky-Molodkina Audiogenic Rat Strain and Identification of Possible Audiogenic Epilepsy-Associated Genes - Chuvakova, Lyubov N.; Funikov, Sergei Yu; Rezvykh, Alexander P.; Davletshin, Artem I.; Evgen’ev, Michael B.; Litvinova, Svetlana A.; Fedotova, Irina B.; Poletaeva, Inga I.; Garbuz, David G. (Frontiers in Molecular Neuroscience, 2021)
Audiogenic epilepsy (AE), inherent to several rodent strains is widely studied as a model of generalized convulsive epilepsy. The molecular mechanisms that determine the manifestation of AE are not well understood. In the present work, we compared transcriptomes from the corpora quadrigemina in the midbrain zone, which are crucial for AE development, to identify genes associated with the AE phenotype. Three rat strains without sound exposure were compared: Krushinsky-Molodkina (KM) strain (100% AE-prone); Wistar outbred rat strain (non-AE prone) and “0” strain (partially AE-prone), selected from F2 KM x Wistar hybrids for their lack of AE. The findings showed that the KM strain gene expression profile exhibited a number of characteristics that differed from those of the Wistar and “0” strain profiles. In particular, the KM rats showed increased expression of a number of genes involved in the positive regulation of the MAPK signalling cascade and genes involved in the positive regulation of apoptotic processes. Another characteristic of the KM strain which differed from that of the Wistar and “0” rats was a multi-fold increase in the expression level of the Ttr gene and a significant decrease in the expression of the Msh3 gene. Decreased expression of a number of oxidative phosphorylation-related genes and a few other genes was also identified in the KM strain. Our data confirm the complex multigenic nature of AE inheritance in rodents. A comparison with data obtained from other independently selected AE-prone rodent strains suggests some common causes for the formation of the audiogenic phenotype.